"Ich habe nur eine Zeit, die Weltzeit." Eine Untersuchung zu Husserls Zeitanalysen - Donyai, Zahra (Studien zur Phänomenologie und Praktischen Philosophie, 2021)
It is a widespread belief that Husserl's conception of time obstructs the way to understanding world-time in a heideggerian sense. Unfolding world-time as one of the main topics of the last phases of Husserl's analyses of time shall refute this criticism. The process of concretization of the transcendental ego also expresses the silent concretization of the world of phenomenology, and these concretizations lead to the topic of world-time. The study assumes that Husserl's phenomenology undergoes a process of concretization with its peak in the theme of world-time.